1996
DOI: 10.1016/s1074-7613(00)80300-3
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Tyrosine Phosphatase HCP by the Killer Cell Inhibitory Receptor

Abstract: Cytolysis of target cells by natural killer (NK) cells and by some cytotoxic T cells occurs unless prevented by inhibitory receptors that recognize MHC class I on target cells. Human NK cells express a p58 inhibitory receptor specific for HLA-C. We report association of the tyrosine phosphatase HCP with the p58 receptor in NK cells. HCP association was dependent on tyrosine phosphorylation of p58. Phosphotyrosyl peptides corresponding to the p58 tail bound and activated HCP in vitro. Furthermore, introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
417
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 582 publications
(437 citation statements)
references
References 54 publications
16
417
4
Order By: Relevance
“…Other cell surface receptors bind to SHP-1 in hemopoietic cells (Yi et al, 1993a;Klinmuller et al, 1995;Pani et al, 1995;Burshtyn et al, 1996). Binding of SHP-1 to the ITIM sequence in all these cell surface proteins terminates signalling with profound e ects on cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cell surface receptors bind to SHP-1 in hemopoietic cells (Yi et al, 1993a;Klinmuller et al, 1995;Pani et al, 1995;Burshtyn et al, 1996). Binding of SHP-1 to the ITIM sequence in all these cell surface proteins terminates signalling with profound e ects on cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in contrast to ITAMs, only one tyrosine of Bgp (Tyr 488 ) was convincingly shown to undergo phosphorylation in cells treated with insulin or with the protein tyrosine phosphatase inhibitor vanadate . Recently, several hematopoietic cell surface receptors, such as the erythropoietin receptor (Klinmuller et al, 1995), the IL-3 receptor, Kit (Yi et al, 1993a,b), FcgRIIB1, the natural killer receptor p58 and B cell antigen receptor (D'Ambrosio et al, 1995;Pani et al, 1995;Burshtyn et al, 1996) have been shown to contain a so-called Immunoreceptor Tyrosine-based Inhibition Motif (ITIM) (D'Ambrosio et al, 1995;Burshtyn et al, 1996). This motif is shorter than that of the ITAMs (Figure 1c) and encompasses a single phosphorylated tyrosine residue followed at position +2 relative to the tyrosine by an obligate leucine.…”
Section: Introductionmentioning
confidence: 99%
“…As expected from studies that established the molecular bases of the affinity of SH2 domains of other molecules for tyrosyl-phosphorylated peptides, the affinity of pITIMs for the SH2 domains of these phosphatases required the conservation of both the Y and the Y+3 residues. Synthetic peptides corresponding to pITIMs of all ITIMbearing molecules were found to bind SHP-1 and SHP-2 in vitro (D'Ambrosio et al, 1995;Burshtyn et al, 1996). The in vitro binding of SHP-1 and SHP-2 to the pITIMs of KIR2DL3 and FcγRIIB depends on the Y-2 residue (Vély et al, 1997).…”
Section: The Y+2 Leucine Determines the Affinity Of The Fcγriib Itim mentioning
confidence: 98%
“…This condition is fulfilled in vitro when beads are coated with sufficient amounts of pITIMs or in vivo when two tandem pITIMs are present in the intracytoplasmic domain of inhibitory receptors such as KIR2DL3. The deletion (Bruhns et al, 1999) or the mutation (Burshtyn et al, 1996) of either ITIM indeed abrogated the ability of KIR2DL3 to recruit SHP-1. This is not fulfilled by FcγRIIB when co-aggregated with activating receptors.…”
Section: The Density Of Pitim Determines the Selective Recruitment Ofmentioning
confidence: 99%
“…A number of membrane molecules have been found to associate with SHP-1 via its SH2 domains, including receptors of hematopoietic growth factors and cytokines, [21][22][23][24][25] subunits of the B cell antigen receptors [26][27][28][29] and the inhibitory receptor of natural killer cells. 30 The functional significance of these associations is underscored by the increased signaling from these membrane molecules in motheaten hematopoietic cells which lack functional SHP-1. 24,28,[31][32][33][34] It is believed that the increased signaling due to loss of the negative regulatory SHP-1 leads to hyperproliferation and organ infiltration of hematopoietic cells in these mice.…”
Section: Introductionmentioning
confidence: 99%